2021
DOI: 10.5194/amt-14-5179-2021
|View full text |Cite
|
Sign up to set email alerts
|

Species correlation measurements in turbulent flare plumes: considerations for field measurements

Abstract: Abstract. Field measurement of flare emissions in turbulent flare plumes is an important and complex challenge. Incomplete combustion from these processes results in emissions of black carbon, unburnt fuels (methane), CO2, and other pollutants. Many field measurement approaches necessarily assume that combustion species are spatially and/or temporally correlated in the plume, such that simple species ratios can be used to close a carbon balance to calculate species emission factors and flare conversion efficie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Although VIIRS provides global flare volume information for flares large enough to be viewed from space, this product does not evaluate flare performance. The operation of individual flares in response to specific environmental and gas composition variables has been evaluated in laboratory and testing facility studies (19)(20)(21)(22)(23)(24)(25), however, only a handful of in situ measurements to characterize performance (i.e., efficiency) have been made of real-world flares (26)(27)(28)(29)(30). A smaller subset of these studies estimate flaring efficiency in terms of CH 4 removal.…”
mentioning
confidence: 99%
“…Although VIIRS provides global flare volume information for flares large enough to be viewed from space, this product does not evaluate flare performance. The operation of individual flares in response to specific environmental and gas composition variables has been evaluated in laboratory and testing facility studies (19)(20)(21)(22)(23)(24)(25), however, only a handful of in situ measurements to characterize performance (i.e., efficiency) have been made of real-world flares (26)(27)(28)(29)(30). A smaller subset of these studies estimate flaring efficiency in terms of CH 4 removal.…”
mentioning
confidence: 99%
“…Gas volumes from flares observable from space are estimated across the globe using measurements from the Visible Infrared Imaging Radiometer Suite (VIIRS) instrument. , Using nitrogen dioxide (NO 2 ) as a proxy for NOx, flaring trends have also been investigated using satellite retrievals in regions such as the Artic, Mexico, and Russia . Investigations into the relationships between flare performance and parameters such as flare design, fuel composition, and crosswinds have been mostly conducted in laboratory and test facilities. Quantifying NOx flaring emission rates as part of a Texas Commission on Environmental Quality (TCEQ) 2010 study, Torres et al measured NOx formation from industrial flares under low flow conditions (0.1%–0.25% of maximum flow), finding emission differences between steam and air-assisted flares . More recently, Shaw et al characterized flaring efficiencies and NOx emission ratios for 58 plumes from offshore facilities in the North Sea, with the largest from floating production and offloading vessels …”
Section: Introductionmentioning
confidence: 99%
“…BC emission rates from individual flares can vary by scale several orders of magnitude (Conrad and Johnson 2017;Weyant et al 2016) and likely vary strongly with operating conditions and flare gas composition. In addition, differences in estimated magnitudes of emissions rates among studies may be at least partially related to under sampling in techniques relying on extractive samples from the plume (Seymour and Johnson 2021). However, it seems likely that BC emissions account for less than 0.5% of the total carbon mass in the fuel for propanefueled flares (Torres et al 2012b;Ellzey et al 1990;Pohl et al 1986) and < 0.1% for flares burning methane-dominated fuel mixtures (McEwen and Johnson 2012).…”
Section: Black Carbonmentioning
confidence: 99%
“…McEwen and Johnson (2012), citing other authors, suggested that efficiency measurements using single point sampling of an inhomogeneous flare plume may be challenged to accurately represent overall combustion efficiency of vertical, pilot scale flares (Pohl et al 1986) and laboratory scale flares in a crosswind (Howell 2004;Poudenx 2000). Recent experiments and analysis by Seymour and Johnson (2021) have shown that H2O and BC volume fractions can independently vary within in a turbulent plume, such that single point sampling methods relying on fixed ratios of species to complete a mass balance can be prone to error if sampling periods are short and/or sample numbers are small.…”
Section: Early Research On Flaresmentioning
confidence: 99%
See 1 more Smart Citation